Convenient new and efficient commercial synthetic route for dasatinib (sprycel®) - Suresh, Garbapu; Nadh, Ratnakaram Venkata; Srinivasu, Navuluri; Yennity, Durgaprasad (Synthetic Communications, 2017)
A new and efficient synthetic route for dual Src/Abl kinase inhibitor Dasatinib (Sprycel®), an anticancer drug, is described. This commercially viable process yields Dasatinib monohydrate free of potential impurities with consistent yield of 68% in route A and 61% in route B with HPLC purity >99.80% over 4 stages.